Analisis Kinerja Keuangan Perusahaan pada PT. Japfa Comfeed Indonesia Tbk - Jezzyca Ria Paramita; Iwan Eka Putra; Abd Halim; Ermaini Ermaini (J-MAS (Jurnal Manajemen dan Sains), 2020)
Financial performance is an overview of how a company's financial condition is. To assess financial performance is used with a benchmark commonly called financial ratios. Financial ratios used are usually such as profitability ratio, liquidity ratio and solvency ratio. in addition to using financial ratios, the company can also use the Altman Z-Score method to assess the level of the company's bankruptcy prediction. This research aims to find out the financial performance of PT Japfa Comfeed Indonesia Tbk as well as the company's future bankruptcy predictions. the research method used is quantitative analysis based on secondary data taken from the Financial Statements of PT Japfa Comfeed Indonesia Tbk for the period 2014 to 2019. The results of the study are measurements of the company's financial ratio showing sufficient value while measurements using the company's Altman Z-Score method show healthy value which means it does not go into bankruptcy.